Higher Beetle Diversity in Native Vegetation Than in Stands of the Invasive Arundo, Arundo donax L., along the Rio Grande Basin in Texas, USA. Issue 3 (12th June 2018) - Osbrink, W L A; Thomas, D B; Goolsby, J A; Showler, A T; Leal, B
Abstract: Within the cattle fever tick quarantine zone along the Rio Grande, a steady displacement of native vegetation by Arundo donax L. has been occurring for over a century. Arundo rapidly grows to a height of 3–6 m creating a dense wall of vegetation impeding surveillance and interception of stray cattle breaching the cattle fever tick quarantine from Mexico. Additionally, arundo monocultures may decrease the number and diversity of predatory beetles feeding on cattle fever ticks. To compare predatory beetle abundance and diversity within and between arundo and native vegetation, beetles were trapped at 10 locations twice a month for 16 mo (=38, 400 trap nights) in the cattle fever tick quarantine zone along the Mexico-American border between Brownsville and Del Rio, TX. In total, 766 beetles were trapped, which included 34 genera and 43 species. Native vegetation provided more beetles, greater species richness, and increased biological diversity. Thus, greater beetle diversity was found in the more complex native vegetation compared with arundo stands. However, because predatory beetle sample numbers were modest, it is unlikely these mostly polyphagous, opportunistic arthropod predators would apply much pressure on tick populations, leading us to conclude that beetle predation would have little effect on tick populations in native vegetation or within stands of arundo.